FAITH INTERSECTION: THE ENCOUNTER OF ISLAMIC FAITH AND CATHOLICISM IN FOSTERING TRUE RELIGIOUS MODERATION (International Conference on Social and Islamic Studies, 2021)
This investigation on the meeting point of islamic faith and Catholicism in fostering true religious moderation aims to discover a common ground in a normative and substantial manner in order to minimize disharmony in the relationship between adherents of Islam and those of Catholicism. The main research question to be explored is: What is the pattern of faith intersections that lies underneath Islam and Catholicism in cultivating true religious moderation? The exploration is a genuine library research with a descriptive-analytical structure. The method employed in this inquiry is manuscript review, which is conducted in arational theological approach. The theoretical framework used is mainly related to the theory of inclusiveness. On the whole, this research is qualitative in nature, focusing on a comparative analysis of the concept of faith intersection between Islam and Catholicism. The results of this study indicate that first, the encounter of faith is exoteric in nature, wherein they share belief inthe six pillars of faith. Second, the two religions also have esoteric and historical encounters. Third, the intersection of faith between Islam and Catholicism lies on their mission as religionsof salvation. Both religions believe in the same doctrine of the Oneness of God as the Authority above all beings, granting salvation to whomever He wills. Fourth, to create true religious moderation, all religious adherents from both Muslim and Catholic circles, starting from the congregation to religious leaders, are expected to hold pluralistic religious viewpoints, esoteric theological outlook, and synchronistic sociological attitudes in fostering harmony in living together so as to develop a safe and peaceful religious as well as national life,which is filled with tolerance on the basis of love.